Method Modification Study for the Thermo Scientific SureTect™ Listeria Species Assay–Matrix Extension. (27th November 2019) - Cloke, Jonathan; Evans, Katharine; Crabtree, David; Hughes, Annette; Simpson, Helen; Holopainen, Jani; Wickstrand, Nina; Kauppinen, Mikko; Leon-Velarde, Carlos; Larson, Nathan; Dave, Keron; Chen, Yi; et al.
Abstract: The Thermo Scientific™ SureTect™ Listeria species assay is a new real-time PCR assay for the detection of all species of Listeria in food and environmental samples. The assay was originally certified as Performance Tested Methods SM (PTM) 071304 in 2013. This report details the method modification study undertaken to extend the performance claims of the assay for matrixes of raw ground turkey, raw ground pork, bagged lettuce, raw pork sausages, pasteurized 2% fat milk, raw cod, pasteurized brie cheese, and ice cream. The method modification study was conducted using the AOAC Research Institute (RI) PTM program to validate the SureTect PCR assay in comparison to the reference method detailed in ISO 11290-1:1996 including amendment 1:2004. All matrixes were tested by Thermo Fisher Scientific (Basingstoke, United Kingdom). In addition, three matrixes (raw cod, bagged lettuce, and pasteurized brie cheese) were analyzed independently as part of the AOAC RI-controlled independent laboratory study by the University of Guelph, Canada. Using probability of detection statistical analysis, there was no significant difference in the performance between the SureTect assay and the International Organization for Standardization reference method for any of the matrixes analyzed in this study.